2013
DOI: 10.1007/s40258-013-0060-y
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Burden of Complications Occurring in Major Surgical Procedures: a Systematic Review

Abstract: The overall conclusions of included studies are consistent: complications represent an important economic burden for health care providers. We conclude that more accurate and consistent data collection is required to serve as input for good-quality economic analyses, which in turn can inform hospital decisions on cost-efficient allocation of their limited resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 57 publications
1
48
1
3
Order By: Relevance
“…The development of post‐operative liver failure was associated with the highest costs. Our review found strong evidence concerning the association of length of stay with costs, a finding supported by others …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The development of post‐operative liver failure was associated with the highest costs. Our review found strong evidence concerning the association of length of stay with costs, a finding supported by others …”
Section: Discussionsupporting
confidence: 88%
“…Our review found strong evidence concerning the association of length of stay with costs, a finding supported by others. 23 Large variations in the inclusiveness of hospital cost existed across the studies, with some studies opting to report charges as opposed to hospital cost. This proved problematic for comparison between studies, as charges are a poor substitution for hospital cost, given the considerable variation seen between healthcare systems and even hospitals in the same healthcare system.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] The cost of surgical resection varies by as much as 130% between hospitals. 5 Because inpatient surgical costs are largely driven by the occurrence of postoperative complications, [9][10][11][12][13] cost variation is intimately related to hospital quality. 14 A patient's age, comorbidities, and functional status may also affect the costs of care by affecting both a patient's likelihood of experiencing a complication and the difficulty of subsequent recovery.…”
Section: Introductionmentioning
confidence: 99%
“…The cost of pancreatic surgery has been found to be associated with complications, surgeon experience, post‐operative pathways, volume and type of operation. For example, post‐operative complications have been found to be consistently associated with increased hospital costs . In contrast, factors associated with decreased costs include hospital volume, clinical pathways and surgeon experience …”
Section: Introductionmentioning
confidence: 99%
“…For example, post-operative complications have been found to be consistently associated with increased hospital costs. 8,14,15 In contrast, factors associated with decreased costs include hospital volume, 15 clinical pathways 16 and surgeon experience. 17 Although Vollmer reported significant programmatic revenue for a high-volume programme, he did not describe the relationship between clinical factors and revenue.…”
Section: Introductionmentioning
confidence: 99%